Literature Review: Content Analysis And Synthesis Of Natural Dyes In Food And Beverages Circulating In The Community - Ravelliani, Andien; Sari, Lala Komala; Marlian, Hermin; Marisah, Marisah; Utami, Marsah Rahmawati; Nurfadhila, Lina (Sean Institute, 2022)
Food additives are ingredients added to food to improve color, shape, taste and texture, as well as to extend the shelf life, and are not the main ingredient. Colorants are often used to increase the attractiveness of food and drinks. There are generally two types of dyes, namely natural dyes and synthetic dyes. The method used in this literature review is derived from 16 journals from reliable sources. The results show of the 16 food and beverage samples used, there were 3 negative results of food and beverage ingredients that were prohibited from being used in food products and 13 of them were positive for containing prohibited food ingredients and exceeding the maximum dose permitted in accordance with existing regulations.